1999
DOI: 10.1128/aem.65.9.3942-3949.1999
|View full text |Cite
|
Sign up to set email alerts
|

Long-Chain Polyphosphate Causes Cell Lysis and Inhibits Bacillus cereus Septum Formation, Which Is Dependent on Divalent Cations

Abstract: We investigated the cellular mechanisms that led to growth inhibition, morphological changes, and lysis of Bacillus cereus WSBC 10030 when it was challenged with a long-chain polyphosphate (polyP). At a concentration of 0.1% or higher, polyP had a bacteriocidal effect on log-phase cells, in which it induced rapid lysis and reductions in viable cell counts of up to 3 log units. The cellular debris consisted of empty cell wall cylinders and polar caps, suggesting that polyP-induced lysis was spatially specific. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 33 publications
0
44
0
2
Order By: Relevance
“…Short-chain-length polyphosphates have been shown to enhance the proliferation of human fibroblasts by stabilizing fibroblast growth factors 13 and exert antibacterial effects against microorganisms. [14][15][16][17] The present study showed that longchain (chain length ≥ 450) polyphosphates improved the intestinal barrier function under conditions of oxidative stress, while shortchain polyphosphates (chain length ≤ 65) exerted no significant effect on the intestinal barrier function. We therefore developed a procedure for fashioning long-chain polyphosphates for clinical trials and conducted the first-in-human trial to assess the outcomes of long-chain polyphosphate therapy for refractory UC in 10 patients who responded poorly to currently available treatments.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Short-chain-length polyphosphates have been shown to enhance the proliferation of human fibroblasts by stabilizing fibroblast growth factors 13 and exert antibacterial effects against microorganisms. [14][15][16][17] The present study showed that longchain (chain length ≥ 450) polyphosphates improved the intestinal barrier function under conditions of oxidative stress, while shortchain polyphosphates (chain length ≤ 65) exerted no significant effect on the intestinal barrier function. We therefore developed a procedure for fashioning long-chain polyphosphates for clinical trials and conducted the first-in-human trial to assess the outcomes of long-chain polyphosphate therapy for refractory UC in 10 patients who responded poorly to currently available treatments.…”
Section: Discussionmentioning
confidence: 50%
“…[10][11][12] This was the first study to show that long-chain polyphosphate was able to improve the intestinal barrier function and ameliorate intestinal injury under inflammatory conditions, although short-polyphosphate is known to enhance the proliferation of human fibroblasts by stabilizing fibroblast growth factors 13 and to exert antibacterial activity against many bacteria and fungi. [14][15][16][17] A subsequent study also showed that polyphosphate produced by a marine cyanobacterium, Synechococcus, exerted an antiinflammatory function. 18 The present study identified the most suitable chain length of polyphosphate for the enhancement of the intestinal barrier function and confirmed the efficacy of long-chain polyphosphate in inflammation models (including a genetically induced mouse colitis model and inflammation-induced human macrophages).…”
mentioning
confidence: 95%
“…However, in the cases where phosphate and pH levels have been carefully monitored in relation to microbial inhibition, a controversial theory has begun to take shape, where phosphate ions alone can be either bacteriostatic or bactericidal. [26][27][28] Previously, we have demonstrated that a novel calcium phosphate glass (CPG), part of the CaO-P 2 O 5 -NaF-MgO-ZnO system, has osteoconductive and resorbable characteristics in vivo. 29,30 In particular, studies by Lee et al 30 have demonstrated that glasses with a Ca/P molar ratio of 0.6 increased mineralization and alkaline phosphatase activity of MC3T3 cells, a preosteoblast-like cell line.…”
Section: Introductionmentioning
confidence: 99%
“…Long-chain phosphates have better inhibitory eff ects than shortchain phosphates. Also, the inhibitory eff ect can be infl uenced by temperature and pH (higher sensitivity when pH > 7.4), the initial population of microorganisms or the addition of metal ions (Jen and Shelef, 1986;Lee et al, 1994a;Zaika et al, 1997;Maier et al, 1999). The eff ect on long-chain polyphosphates works according to the principle of chelation of mainly divalent metal ions (Ca 2+ a Mg 2+ ), which are essential for maintaining the integrity of cell walls in gram-positive bacteria by forming transverse bridges between the molecules of teichoic acid in a cell wall (Lee et al, 1994b).…”
mentioning
confidence: 99%
“…Chelation of divalent ions can also cause these ions to be inactive to some essential physiological processes of growth. It has been found out that the protein responsible for the formation of septum during cell division (FtsZ protein) has a GTP activity, which is strictly dependent on the presence of magnesium ions (Maier et al, 1999). An elimination of the above-mentioned ions results in a bactericidal and bacteriolytic eff ect (Lee et al, 1994b;Maier et al, 1999).…”
mentioning
confidence: 99%